STREAM OF CONSCIOUSNESS IN THE ARABIC NOVEL BETWEEN TEXTUAL STUDY AND SOURCE STUDY: AN APPROACH TO STRUCTURE, STYLES AND SOURCES - Hatem Ali Abdel Zaher Abu Amra Hassan Youssef (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
The article explains how stream of consciousness serves as a link between textual analysis and source studies in modern Arabic fiction. It examines internal narrative structures, psychological time, and the Western and Arabic influences behind this technique. It also highlights the role of stream of consciousness in modernizing narrative form and character construction.